1979
DOI: 10.1111/j.1528-1157.1979.tb04854.x
|View full text |Cite
|
Sign up to set email alerts
|

Tears as the Best Practical Indicator of the Unbound Fraction of an Anticonvulsant Drug

Abstract: Phenobarbital and carbamazepine concentrations were determined by the EMIT technique in tears, saliva, cerebrospinal fluid (CSF), and plasma of patients with epilepsy. Closer correlation was shown between tear/plasma and tear/CSF ratios than between saliva/plasma and saliva/CSF ratios for the two agents. The phenobarbital CSF/serum ratio was in good agreement with data in the literature, and the higher ratio found for carbamazepine may be caused by an EMIT assay cross-reaction for the free fraction of carbamaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…A significant portion of the agent passed through loose junctions of the acinous epithelium presents in lachrymal glands. Carbamazepine and phenobarbital levels in tears are twice lower than in plasma [3,97]. Stoehr et al [98] have observed a stronger correlation with plasma versus tears (r = 0.94) than with plasma versus saliva (r = 0.84).…”
Section: Determination Of Drugs Administered By General Route For a Smentioning
confidence: 91%
See 3 more Smart Citations
“…A significant portion of the agent passed through loose junctions of the acinous epithelium presents in lachrymal glands. Carbamazepine and phenobarbital levels in tears are twice lower than in plasma [3,97]. Stoehr et al [98] have observed a stronger correlation with plasma versus tears (r = 0.94) than with plasma versus saliva (r = 0.84).…”
Section: Determination Of Drugs Administered By General Route For a Smentioning
confidence: 91%
“…Standardisation of experimental procedure may hinder tearing reflex or evaporation and ensures stability of the compounds determined in lachrymal fluid [3]. Different procedures have been proposed.…”
Section: Preparation Of Tear Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma and mixed saliva samples were collected for each patient immediately before and 15 and 45 min after intravenous administration of single dose (1200 mg) of sodium valproate (Sigma-Tau, Italy). The plasma and saliva levels of (Schottelius, 1978;Monaco et al, 1979;Paxton & Donald, 1980). Valproic acid in plasma was determined in duplicate by gas-liquid chromatography (Kupferberg, 1978).…”
Section: Morgan Db and Swaminathan R (1981)mentioning
confidence: 99%